Evaluation of the Osteoinductive Capacity of Canine Demineralized Bone Matrix in Heterotopic Muscle Sites of Athymic Rats - Forell, Elaine B.; Straw, R. C.; Powers, Barbara E.; Johnson, J.; Cooper, Mary F.; Withrow, St. J. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
The osteoinductive capacity of canine demineralized bone matrix (DBM), implanted in epaxial muscle sites of athymic rats, was evaluated using calcium content and histomorphometry at two, four and six weeks after implantation. Results of this study confirm that DBM, derived from canine sources, does possess significant osteoinductive ability since histological examination revealed the presence of new cartilage, bone, or both, at 21/24 implantation sites. The osteogenesis induced by canine DBM continued as an active, cumulative process throughout the six week investigation period. The mean percentage of total induced osteogenic components including new, live cartilage, woven bone, lamellar bone and bone marrow cellular elements, was significantly greater after six weeks than after two weeks of implantation (p <0.01). Comparison of histomorphometric point counts at two, four and six weeks of implantation supported the conclusion that bone for mation as induced by canine DBM, proceeds primarily via an endochondral ossification pathway. Although the amount of calcium deposited in tissues harvested from DBM implanted sites tended to increase as implantation time lengthened, there was not a statistically significant correlation between calcium content and the level of osteogenic activity seen histologically (r = 0.32, p = 0.13).The osteoinductive capacity of canine demineralized bone matrix (DBM), implanted in ep-axial muscle sites of athymic rats, was evaluated using calcium content and histomorphometry at two, four and six weeks after implantation. Results of this investigation confirm that DBM, derived from canine sources, does possess significant osteo-inductive ability and that bone formation proceeds primarily via a pathway of endochondral ossification.
Keywords: Canine; osteoinduction; demineralized bone matrix